Two-Step Synthesis of Some Novel Monoindolylmaleimides - Zhong, Jian; Jia, Ping; Xu, Shan; Han, Liang; Li, Yujing; Gao, Jianrong; Ye, Qing (Asian Journal of Chemistry, 2014)
Monoindolylmaleimides have been identified as potent glycogen synthase kinase-3b inhibitors. In this paper, a convenient methodology for the preparation of some new monoindolylmaleimides was developed by microwave assisted condensation of substituted monochloromaleimides with N-containing heterocycles followed by ammonolysis in good overall yield (up to 80 %). The products were characterized by 1H NMR and ESI-MS.